The Use of Nepali in Secondary-Level English Classrooms: Challenges and Strategies for Promoting English Medium Interaction (SMC Journal Shadananda Multiple Campus, 2026)
As part of a mini-research conducted in Shadananda Municipality, Bhojpur district, this article examines the role of Nepali in secondary-level English classrooms in a rural multilingual context. The study is guided by two research questions: what factors influence Nepali use in English classrooms, and how teachers, students, and parents perceive the challenges and strategies for promoting English-medium interaction. The study follows a qualitative, exploratory research design and uses purposive sampling to select 12 students from two secondary schools: grade 10 students from Arun Secondary School and grade 12 students from Shadananda Secondary School. Data were collected through classroom observations, semi structured interviews with teachers, and focus group discussions with parents, and analyzed by developing codes, categories, and themes that reflect classroom practices and stakeholder perceptions. The study reveals that English-medium instruction is implemented in a mixed-mode approach, with Nepali frequently used to mediate classroom communication. The findings highlight challenges in teachers’ fluency and student confidence, classroom management, and the lack of an English-friendly environment. The study concludes that promoting English interaction requires a balanced and context-sensitive approach. It recommends structured activities, role-plays, group discussions, a gradual increase in English input, teacher training, student-oriented confidence-building tasks, and institutional support.